Prevalence of Hearing Loss among Noise Exposed Industrial Workers - Rahman, Md Shafiq Ur; Biswas, Nripendra Nath; Alam, Shahbub; Roy, Debabrota; Rahman, ATM Sumaief Ur; Rudra, Ranjit Kumar; Rahman, BM Lutfar; Arefin, Md Muktadir; Ahmad, Molla Sharfuddin; Murshed, S M Munawar (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Exposure to any type of noise has a potential risk. Higher the level of noise and longer duration of exposure, more the risk for hearing sensitivity and health as a whole. Occupational noise induced hearing loss (ONIHL) is a major cause of disability throughout the world. So this study was designed to know the prevalence of NIHL among the noise exposed industrial workers in Bangladesh. A prospective observational study of 377 People working at industrial environment in Jute mills at Faridpur region were studied between January 2021 to June 2021. Data collected from each respondent recorded on a predesigned data collection form. Pure tone audiometry was performed in both ears. Among 377 study population, 157(41.6%) subjects had hearing loss and 220 subjects (58.4%) had no loss. Among the workers with hearing loss, 98(62.4%) got hearing loss on both sides, 32(20.4%) on the right side and 27(17.2%) on the left side. Among them 83(52.9%) had mild hearing loss, 37(23.6%) had moderate hearing loss, 31(19.7%) had severe hearing loss and 6(3.8%) had profound hearing loss. The average duration of work in the industry was 6.94±5.64 years and majority (78.5%) had 8 hours working hour per day and 21.5% had more than 8 hours. The average sound intensity was 91.51±8.12 dB(A) with 10.9% exposed to <_85 dB(A) and 89.1% to >85 dB(A). This study shows Noise-induced hearing loss (NIHL)as highly prevalent among noise-exposed workers in Bangladesh. Age >35 years, high noise level, exposure of more than 10 years, were significantly associated with increased risk of hearing loss. The local and national authority should focus on noise monitoring, engineering modifications of buildings and machinery, occupational safety policies, administrative controls, providing education on NIHL, periodic audiometric assessments and follow-up evaluation for hearing threshold shift. This study supported the elements for further research studies related to the employer compliance with occupational health and safety regulations to address awareness of their responsibility in minimizing hazards in workplaces. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):90-95